Pattern of Indirect Immunofluorescence Assay Antinuclear Antibody in Pediatric Lupus Nephritis - Fadhila Novianti; Reni Ghrahani; Noormarina Indraswari (Faculty of Medicine Universitas Padjadjaran, 2020)
Objective: To determine the association between Anti-Nuclear Antibody (ANA) pattern in pediatric Systemic Lupus Erythematosus (SLE) patients and proteinuria as a sign of renal involvement in SLE.Methods: This was a cross-sectional study, using data from medical records involving 89 newly diagnosed with SLE (aged ≤ 18 years) in Department of Child Health Dr. Hasan Sadikin General Hospital, Bandung, from January 1st 2018 to June 30th 2019. Data of ANA pattern and proteinuria were collected from medical record. ANA pattern was examined by Immunofluorescence Assay (IFA) method. Chi-square was used to analyze the association between ANA pattern and proteinuria as a sign of renal involvement in pediatric SLE patients.Results: There were 89 patients, consisting of 7 male (7.9%) and 82 female (92.%) with median age of 14 (IQR=12-16). There were only 44 pattern of ANA as follow: homogenous 56.8%, speckled 36.4%, and nucleolar 6.8%. However, there is no significant association between homogenous pattern with proteinuria events (p=0.831).Conclusions: Homogenous pattern was the most frequent ANA pattern in children with SLE, and the pattern has no association with proteinuria events.